The influence of vehicles speed on accident rates and their consequences - Pikūnas, Alvydas; Pumputis, Vidmantas; Sadauskas, Vigilijus (Transport, 2004)
The purpose of this article is to identify the influence of vehicles speed on accident rates and their consequences. In general the desired speed depends on several factors such as speed limits, vehicle type, traffic density, road environment, road geometry, time, and driving experience. From traffic engineering point of view a drivers’ desired speed is the speed, which drivers usually want to maintain in different traffic situations, but it's very important to create a safe environment for all participants of traffic. When traffic is heavy most drivers are in a platoon and the traffic situation is such that some drivers attempt to overtake the leading vehicle or adjust their speed to the vehicle in front. Drivers cannot achieve the desired speed during peak hours. During peak hours urban freeways usually have severe traffic congestion. The random variation of traffic also contributes to the fact that it is not always possible to maintain the speed which a driver desires.First Published Online: 27 Oct 2010